On the seam welding of ultra-thin commercially pure (CP) grade-2 titanium foils. Issue 7 (2nd September 2021) - Kumar, Aniruddha; Neogy, Suman; Bhatt, R. B.
ABSTRACT: This communication reports a comparative study on the seam welding of CP grade-2 Ti foils with thicknesses of 10 µm, 50 µm and 100 µm using a repetitive nanosecond pulsed fibre laser and a lamp-pumped pulsed Nd-YAG laser. The welding was accomplished in a lap joint configuration. A fine acicular microstructure was observed in the welds made by the nano second fibre laser, whilst a coarse basket weave microstructure was observed in the welds made by the Nd-YAG laser. The tensile properties of the welds carried out by the nano-second fibre laser was found to be superior with respect to the welds carried out by the pulsed Nd-YAG laser. Welds made by the nano-second fibre laser could withstand 17% more load, whereas elongation before fracture was almost double to that of the welds made by the Nd-YAG laser. This variation is comprehensible on the basis of the finer weld microstructure evolved in nanosecond laser welding due to the very low heat input and high cooling rate associated with this process. This study established with certitude that nanosecond duration pulsed fibre lasers are a better choice for welding thin titanium foils in comparison to long pulsed Nd-YAG lasers.